Rivers of Darkness - Hardy, Ronald (New York G.P. Putnams sons, 1979)
Arriving in Mozambique in 1973 to battle a terrifying disease causing blindness, Dr. Harry Lynd and his band of medical missionaries, which includes a former nun now in love with him, are torn between medical ethics and the instinct to survive
Keywords: Fiction